A facile sulfenylchlorination of alkenes with Me2SO/(COCl)2. Issue 4 (16th February 2019) - Lan, Liyuan; Gao, Yang; Ding, Rui; Zhang, Ting; Liu, Yongguo; Sun, Baoguo; Tian, Hongyu
Abstract: The sulfenylchlorination of a series of alkenes is investigated by using the combined reagent of dimethyl sulfoxide and oxalyl chloride. The corresponding β-chloro sulfides were obtained in mediate to good yields. Most of the terminal alkenes give the Markovnikov adducts mainly and the sulfenylchlorination of cyclic alkenes is stereospecific to produce the adducts with trans configuration. Methanesulfenyl chloride is supposed to be the real species for sulfenylchlorination. Graphical Abstract: